Neuroimmune and epigenetic involvement in adolescent binge ethanol‐induced loss of basal forebrain cholinergic neurons: Restoration with voluntary exercise. (18th February 2019) - Vetreno, Ryan P.; Bohnsack, John Peyton; Kusumo, Handojo; Liu, Wen; Pandey, Subhash C.; Crews, Fulton T.
Abstract: Binge drinking and alcohol abuse are common during adolescence and cause lasting pathology. Preclinical rodent studies using the adolescent intermittent ethanol (AIE; 5.0 g/kg, i.g., 2‐day on/2‐day off from postnatal day [P]25 to P55) model of human adolescent binge drinking report decreased basal forebrain cholinergic (ie, ChAT+) neurons that persist into adulthood (ie, P56‐P220). Recent studies link AIE‐induced neuroimmune activation to cholinergic pathology, but the underlying molecular mechanisms contributing to the persistent loss of basal forebrain ChAT+ neurons are unknown. We report here that the AIE‐induced loss of cholinergic neuron markers (ie, ChAT, TrkA, and p75 NTR ), cholinergic neuron shrinkage, and increased expression of the neuroimmune marker pNF‐κB p65 are restored by exercise exposure from P56 to P95 after AIE. Our data reveal that persistently reduced expression of cholinergic neuron markers following AIE is because of the loss of the cholinergic neuron phenotype most likely through an epigenetic mechanism involving DNA methylation and histone 3 lysine 9 dimethylation (H3K9me2). Adolescent intermittent ethanol caused a persistent increase in adult H3K9me2 and DNA methylation at promoter regions of Chat and H3K9me2 of Trka, which was restored by wheel running. Exercise also restored the AIE‐induced reversal learning deficits on the Morris water maze. Together, these data suggest that AIE‐induced adult neuroimmune signaling and cognitive deficits are linked to suppression of Chat and Trka gene expression through epigenetic mechanisms that can be restored by exercise. Exercise restoration of the persistent AIE‐induced phenotypic loss of cholinergic neurons via epigenetic modifications is novel mechanism of neuroplasticity. Abstract : Adolescent intermittent ethanol (AIE), which models human adolescent binge drinking, causes a loss of basal forebrain cholinergic neurons through neuroimmune and epigenetic processes that persists into adulthood. Voluntary wheel running after AIE restored the AIE‐induced neuroimmune and epigenetic processes leading to recovery of basal forebrain cholinergic neurons. Exercise restoration of the persistent AIE‐induced phenotypic loss of cholinergic neurons via epigenetic modifications is novel mechanism of neuroplasticity.